The road drainage against the legal protection of herpetofauna - Półtorak, Małgorzata (Budownictwo i Architektura / Civil and Architectural Engineering, 2016)
Construction of roads causes interference in the environment, resulting in number of ecological changes. Site facilities associated with road structures, including drainage system of a lane, play a significant role among environmental impacts. It affects particular elements of the environment, causing changes in existing ecosystems, in terms of, among others, surface and groundwater, soil, landscape and lively nature. The paper presents impact of a drainage system of a road on animal nature, mainly herpetofauna. Results of a control of a drainage system facilities for the presence of amphibians are shown for selected sections of roads commissioned by General Directorate for National Roads and Motorways Katowice Branch. Basic problems associated with active protection of animals on completed road investments and methods to minimize the impact of drainage system on amphibians are also presented in the paper.